Effect of inorganic and organic nitrogenous sources on soil fertility, nutrient uptake and economics of paddy (Oryza sativa) crop in Indo-Gangetic plains - ROOHI; KUMAR, VIJAY; SUMIT; KUMARI, KIRAN; CHAUDHARY, ANKUR; RAM, MANGAT (The Indian Journal of Agricultural Sciences, 2024)
Present study was carried out during rainy (kharif) seasons of 2021 and 2022 at Rice Research Station, Chaudhary Charan Singh Haryana Agricultural University, Kaul, Haryana to explore the merits of organic farming compared to inorganic farming for sustainable agriculture. The experiment consisting of 7 treatments in paddy (Oryza sativa L.) crop conducted in randomized block design (RBD) with 5 replications. Organic treatments include application of different nitrogenous sources, viz. farmyard manure; green manure (Sesbania); vermicompost and mustard cake on equivalent nitrogen basis and inorganic sources include urea fertilizer. The results revealed that the application of urea as an inorganic nitrogen source resulted in higher status of available nitrogen (171.4 kg/ha), phosphorus (25.56 kg/ha), and potassium (319.2 kg/ha) in soil as compared to other treatments. Similarly, the uptake of NPK by paddy grains was highest in the treatment with 100% nitrogen through urea (43.77 kg/ha, 16.33 kg/ha, and 17.69 kg/ ha, NPK, respectively), being at par with other organic treatments during both the seasons. While higher uptake of NPK (42.5 kg/ha, 19.78 kg/ha, 100.31 kg/ha, respectively) by paddy straw was recorded in treatment where 100% N through inorganic urea was applied. Organic farming system (increase ranged from 22.5 to 29.9%) performed similar to conventional farming (31.2% increased) in terms of yield over absolute control plot. Notably, treatments receiving 150% nitrogen through farmyard manure and 100% nitrogen through urea exhibited higher benefit-to-cost (B:C) ratios of 2.78 and 2.73, respectively. Therefore, organic farming emerges as an environmentally sustainable alternative to conventional practices, contributing to soil health and ensuring a consistent paddy crop yield.